(untitled) (Journal of Bangladesh Academy of Sciences, 2009)
The impact of various dilutions (2.5, 5, 10, 25 and 50%) of paint industry effluent on physico-chemical properties of soil and the germination, growth and dry matter productions of corn (Zea mays L.) and rice (Oryza sativa L.) have been studied. The effluent was acidic and had low BOD and COD values because of its low content of suspended solid. It contained high concentration of calcium, medium concentrations of nitrogen, sodium, potassium, sulphate, chloride and low concentrations of phosphorus, magnesium and bicarbonate. The trace element like Mn, Ni, Cu, Zn and Pb were measured in the Î¼g L-1 level. On irrigation of soil with the effluent an increase in the water soluble salts, pH, electrical conductivity, cation exchange capacity, nitrogen, phosphorus potassium, sodium, calcium, magnesium and iron contents of the soil for effluent concentrations of 2.5, 5 and 10% were observed but all these parameters were found to decrease on treatment of the soil with the effluent concentration of 25% and above. The effluent of the lower concentrations (2.5, 5 and 10%) enhanced the growth of both crops. However, negative effects on seed germination, dry matter production and the yield of both crops were found for the effluent concentration of 25% and above. doi: 10.3329/jbas.v32i1.2441 Journal of Bangladesh Academy of Sciences, Vol. 32, No. 1, 41-53, 2008